165k views
5 votes
Simplify $\frac{-10a^2b^4}{5a^{-9}b^{-5}}$

User Ctbrown
by
6.2k points

1 Answer

6 votes

\bf ~~~~~~~~~~~~\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} \qquad \qquad \cfrac{1}{a^n}\implies a^(-n) \qquad \qquad a^n\implies \cfrac{1}{a^(-n)} \\\\ -------------------------------\\\\ \cfrac{-10a^2b^4}{5a^(-9)b^(-5)}\implies \cfrac{-10}{5}\cdot \cfrac{a^2b^4}{a^(-9)b^(-5)}\implies \cfrac{-2}{1}\cdot \cfrac{a^2a^9b^4b^5}{1} \\\\\\ -2a^(2+9)b^(4+5)\implies -2a^(11)b^9
User Rkg
by
5.1k points